Atendimento às mulheres que buscam pelo exame citopatológico de colo de útero: vivência de enfermeiros da Atenção Primária à Saúde - Silva, Keila Aparecida (2024)
The nurse who is part of the Primary Health Care professional team is responsible for the continuous coordination of services, contributing significantly to the care of the female population. This study aims to analyze the experience of nurses who work in Primary Health Care in relation to care for women seeking cervical cytology examination. In this context, the main clientele of the Unified Health System is women, who have a longer life expectancy than men and are subject to specific pathologies of their physiology, such as cervical cancer. This study aims to analyze the experience of nurses who work in Primary Health Care in relation to care for women seeking cervical cytology examination. This is a qualitative, descriptive, analytical study. Dialectical hermeneutics was adopted as a theoretical-methodological framework for discussing empirical data with theoretical axes. Carried out with 15 nurses working in Primary Care, through semi-structured interviews, in a face-to-face environment, from March to May 2023, guided by an instrument developed by the researchers, composed of items referring to the sociodemographic and professional characterization of the participants and two open questions. Descriptive analysis was used to present data regarding sociodemographic and professional characterization and inductive thematic analysis was used to organize and analyze qualitative data. Approved by the Research Ethics Committee, through Certificate of Presentation of Ethical Appreciation 66824123.6.0000.5142 and Substantiated Opinion 5.922.349. There was a predominance of female nurses, married, aged between 30 and 40 years, working for 10 to 15 years in the Family Health Strategy. The thematic analysis made it possible to define the themes: Care for women in Primary Health Care in relation to the cytopathological examination of the cervix and; Nurse's role in managing and assisting women in the context of cytopathological examination of the cervix. It was learned that there is prioritization of care according to the Women's Health Care Guideline, although all women who seek the service are equally served. There is resistance to adherence to the procedure due to fear, discomfort, shame, beliefs and local culture, which highlights the need to actively seek women to undergo the exam, although assistance resulting from spontaneous demand is also observed. Continuing Education and Health Education must be implemented to define and clarify the objectives of the procedure with professionals and the population. The articulation between assistance and management is positive, however, the administrative/bureaucratic management function, carried out concomitantly with assistance, generates overload and stress and reduces the time for assistance to women, triggering dissatisfaction and frustration among nurses. It highlights the need to rethink the operationalization of Public Policy guidelines relating to Women's Health in accordance with the local reality of each community, to make service to this clientele more individualized, humanized and effective and to re-signify Education in Health, with a view to user autonomy and the implementation of strategies that establish nurses' responsibilities in care management and administrative functions.